Measurement Report: Changes in ammonia emissions since the 18th century in south-eastern Europe inferred from an Elbrus (Caucasus, Russia) ice-core record - M. Legrand; M. Legrand; M. Vorobyev; D. Bokuchava; S. Kutuzov; S. Kutuzov; A. Plach; A. Stohl; A. Khairedinova; V. Mikhalenko; M. Vinogradova; S. Eckhardt; et al. (Atmospheric Chemistry and Physics)
Atmospheric ammonia (NH3) is a key transboundary air pollutant that contributes to the impacts of nitrogen and acidity on terrestrial ecosystems. Ammonia also contributes to the atmospheric aerosol that affects air quality. Emission inventories indicate that NH3 was predominantly emitted by agriculture over the 19th and 20th centuries but, up to now, these estimates have not been compared to long-term observations. To document past atmospheric NH3 pollution in south-eastern Europe, ammonium (NH<msubsup>4+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="310866e2e55ea172cf2d52bb7208ba35"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-1385-2025-ie00001.svg" width="8pt" height="15pt" src="acp-25-1385-2025-ie00001.png"/></svg:svg>) was analysed along an ice core extracted from Mount Elbrus in the Caucasus, Russia. The NH<msubsup>4+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="aa378b71f34a6c23384fc0eb7c6e7621"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-1385-2025-ie00002.svg" width="8pt" height="15pt" src="acp-25-1385-2025-ie00002.png"/></svg:svg> ice-core record indicates a 3.5-fold increase in concentrations between 1750 and 1990 CE. Remaining moderate prior to 1950 CE, the increase then accelerated to reach a maximum in 1989 CE. Comparison between ice-core trends and estimated past emissions using state-of-the-art atmospheric transport modelling of submicron-scale aerosols (FLEXPART (FLEXible PARTicle dispersion) model) indicates good agreement with the course of estimated NH3 emissions from south-eastern Europe since ∼ 1750 CE, with the main contributions from south European Russia, Türkiye, Georgia, and Ukraine. Examination of ice deposited prior to 1850 CE, when agricultural activities remained limited, suggests an NH<msubsup>4+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="a9b2fdba183dceff94210c316afa95ef"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-1385-2025-ie00003.svg" width="8pt" height="15pt" src="acp-25-1385-2025-ie00003.png"/></svg:svg> ice concentration related to natural soil emissions representing ∼ 20 % of the 1980–2009 CE NH<msubsup>4+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="9837b1bc16c7511343fef307428ed3c8"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-1385-2025-ie00004.svg" width="8pt" height="15pt" src="acp-25-1385-2025-ie00004.png"/></svg:svg> level, a level mainly related to current agricultural emissions that almost completely outweigh biogenic emissions from natural soil. These findings on historical NH3 emission trends represent a significant contribution to the understanding of ammonia emissions in Europe over the last 250 years.